Efecto del tipo de muestra en la relación diámetro-altura comercial en los árboles de Pouteria torta (Mart.) Radlk "quinilla" en bosque natural. Puerto Almendra, Loreto, Perú – 2023 - Linares Pizango, Lina de Fatima (2025)
The objective of the study was to determine the allometric model that best fits the diameter - commercial height relationship in Pouteria cake (Mart.) Radlk “quinilla” trees in natural forest according to sample type. Puerto Almendra, Loreto, Peru – 2023. The variables used were diameter and commercial height of trees with DAP ≥ 10 cm; 4 samples were used, sample 1 was 5 diameter classes with 40 individuals; sample 2 with 9 diameter classes and 40 individuals; sample 3 with 20 individuals chosen at random and sample 4 was the representative sample with 30 individuals chosen at random. The results indicate that the Inverse allometric model was the one that presented the best relationship between diameter and commercial height in the samples evaluated for Pouteria cake (Mart.) Radlk “quinilla” trees in natural forest; Furthermore, it was determined that the degree of relationship is excellent between the evaluated variables; It was also defined that the common variations between diameter and commercial height are between 63% and 85%; Likewise, the equation was defined to predict the commercial height of Pouteria cake (Mart.) Radlk “quinilla” trees in natural forest from the diameter of the tree, it is as follows: Y= 15,432 + (-111,721 / t) .